Hubungan antara Stres Akademik dan Kesehatan Mental pada Mahasiswa - Azizatunnisah; Ratna Yunita Setiyani Subardjo (EduInovasi: Journal of Basic Educational Studies, 2024)
This study aims to examine the relationship between academic stress and mental health in university students. Academic stress is often a factor that affects mental health, especially in students who face pressure in academic achievement. This study used descriptive and inferential quantitative approaches with a simple correlation method. A total of 100 active students are currently studying at universities in Indonesia. Data were collected through an online survey google form that measures the level of academic stress and mental health, and distributed through social media and then analyzed using the classical assumption test, Pearson correlation test, and hypothesis testing. The results showed that there is a significant negative relationship between academic stress and students' mental health (r = -0.440, p < 0.01), which means that the higher the academic stress, the worse the mental health condition of students. To meet statistical assumptions, the data underwent linear transformation, which clarified the relationship between the two variables. Although this study went well, there were some limitations, such as the unbalanced number of subjects between genders. Therefore, it is recommended that future studies consider sample balance as well as using longitudinal methods to strengthen the findings. This study makes an important contribution to efforts to improve students' mental health through better academic stress management.